THE AIRPORT DE-ICING OF AIRCRAFTS - Robert KONIECZKA (Scientific Journal of Silesian University of Technology. Series Transport)
This article provides a summary of the issues involved in de-icing several kinds of aircrafts before flight. The basic risks of an iced aircraft and the factors that can influence its intensity are stated. It discusses the methods for de-icing and protecting against ice formation on small aircrafts, helicopters, and large aircrafts. It also classifies the fluids and other methods used for these de-icing operations, and explains the characteristics and limitations of their use.